Co-Relationship Between Age, Religion And Education Level In Supporting “Reuni 212” - Ahmad Zaharuddin Sani Ahmad Sabri; Roziya Abu; Andi Hasriani; Badruddin Kaddas (Journal of Research and Multidisciplinary, 2019)
Reunion 212 rallies in Indonesia is a symbolic rally of an anti-government opposition march. Since the Dec. 2, 2016 rally, there has been other rally organized in 2 December 2017 and the latest in 2 December 2018. In the year 2018, 212 reunions have transformed into a movement not only aim to stop the liberal and leftists coming to power alongside Ahok in Jakarta Governor election, but also pose a challenge to the re-election of President Jokowi in coming parliamentary and presidential election. This objective of the study is to investigate the impact of 212 reunion rally does towards the coming Indonesian presidency choice. Using a list of fix questionnaire survey, 1200 respondents who were the participants of 212 reunion rally in 2 December 2018 gave their feedback. The findings show that there’s is no major significant towards any changes on the people’s choice of presidency. Hence the focus of this paper is to answer the question of why the emergence of this type of social movements specifically Reuni 212 and why are people involved and participating in it. Most importantly to understand if it’s can truly affect the next Indonesia Presidential election.